Answer:
X ≥ 3.5
Step-by-step explanation:
-2x-6≤1
+6 +6
-2x≤7
-2x/2 7/2
x ≥ 3.5
Answer:
(7, - 7 )
Step-by-step explanation:
- 4x + y = - 35 → (1)
- 2x - y = - 7 → (2)
adding the 2 equations term by term will eliminate the y- term
(- 4x - 2x) + (y - y) = - 35 - 7
- 6x + 0 = - 42
- 6x = - 42 ( divide both sides by - 6 )
x = 7
substitute x = 7 into either of the 2 equations and solve for y
substituting into (1)
- 4(7) + y = - 35
- 28 + y = - 35 ( add 28 to both sides )
y = - 7
solution is (7, - 7 )
Answer:
f(x)=5x^3-2x^2-90x-36=0
=x^2(5x-2)-18(5x-2)=(x^2-18)(5x-2)=0
x^2-18=0/5x-2=0
x^2=18=x=9√2
5x-2=0
x=2/5
zeros are 9√2,2/5
Answer:
B and C, only
Step-by-step explanation: